DESIGNING THE INTEGRATED SYSTEM OF RISK MANAGEMENT AND INTERNAL CONTROL NECESSARY FOR MANAGERIAL DECISION-MAKING - Elvira I. Bakhtigozina (Вестник Российского экономического университета имени Г. В. Плеханова)
The article discusses key standard requirements to the system of internal control and puts forward the algorithm of building a reliable system of internal control, which could promote improvement of business organization, timely disclosing, preventing operational, finance and other risks and could allow management to take mature and opportune decisions. The requirement to internal control organization was fixed legally, however methodology of building an effective system of internal control over business activity and accounting is unavailable. The algorithm of building the system of internal control proposed by the author combines legal requirements and practical experience of business entities gained in the process of building the system of internal control.